Identification of the rs797045105 in the SERAC1 Gene by Whole-exome Sequencing in a Patient Suspicious of MEGDEL Syndrome - Mina Zamani; Tahereh Seifi; Jawaher Zeighami; Neda Mazaheri; Emad Jahangirnezhad; Minoo Gholamzadeh; Alireza Sedaghat; Gholamreza Shariati; Hamid Galehdari (Basic and Clinical Neuroscience, 2020)
Introduction: Whole Exome Sequencing (WES) has been increasingly utilized in genetic determinants of various inherited diseases. Methods: We applied WES for a patient presenting 3-Methylglutaconic Aciduria (MEG), Deafness (D), Encephalopathy (E), and Leigh-like (L) syndrome. Then Sanger sequencing was used for the detected variant validation. Results: We found an insertion, rs797045105 (chr6, 158571484, C>CCATG), in the SERAC1 gene with homozygous genotype in the patient and heterozygous genotype in her unaffected parents. Notably, bioinformatics analysis using mutation taster (prob>0.99) and DDIGin (prob=86.51) predicted this mutation as disease-causing. Also, the variant was not present in our database, including 700 exome files. Conclusion: These findings emphasize the pathogenicity of rs797045105 for MEGDEL syndrome. On the other hand, our data shed light on the significance of WES application as a genetic test to identify and characterize the comprehensive spectrum of genetic variation and classification for patients with neuro- metabolic disorders.